问题 解答题
计算:
(1)11-6.5+9-3.5-2
(2)0-(-6)+5-|6-11|
(3)5
1
5
-[
1
6
-(-4.2)-(-
5
6
)]

(4)(-3)×
5
6
×(-
9
5
)×(-
1
3
)

(5)(
1
2
+
1
3
-
1
4
)×(-12)

(6)-
2
3
-[
3
4
-(1
1
2
+
3
4
-2)-
2
3
]

(7)(-36
9
11
1
9
答案

(1)原式=(11+9)+[(-6.5)+(-3.5)+(-2)]=20+(-12)=8;

(2)原式=0+6+5-5=6;

(3)原式=5.2-(

1
6
+4.2+
5
6
)=5.2-5.2=0;

(4)原式=-3×

5
6
×
9
5
×
1
3
=-
3
2

(5)原式=

1
2
×(-12)+
1
3
×(-12)-
1
4
×(-12)=-6-4+3=-7;

(6)原式=-

2
3
-(
3
4
-1
1
2
-
3
4
+2-
2
3
)=-
2
3
-
3
4
+1
1
2
+
3
4
-2+
2
3
=-
1
2

(7)原式=(-36-

9
11
)×
1
9
=-36×
1
9
-
9
11
×
1
9
=-4-
1
11
=-4
1
11

填空题
单项选择题